Perbandingan Sistem Peradilan Tata Usaha Negara dan Conseil d’etat sebagai Institusi Pengawas Tindakan Hukum Tata Usaha Negara - W. Riawan Tjandra (Fakultas Hukum Universitas Islam Indonesia, 2013)
French State Administrative Court system and Indonesian State Administrative Court system basically have many similarities. The legal problem studied in this paper is related to the attempt to widely manage the judge proactivity principle in the State Administrative Court to attribute the advisory function of the State Administrative Court as a part of active dimensions of the preventive control of the State Administrative Court toward the state administrative staff before a State Administrative Decision is stipulated. The research method used to discuss the problem is the normative legal research using legal comparative approach. The result of the study concludes that there is a necessity to broaden the function of State Administrative Court in Indonesia to increase the quality of the state administrative decisions issued by the state administrative authorities.